Penerapan Bimbingan Belajar Untuk Meningkatkan Prestasi Belajar Bagi Siswa Yang Mengalami Kesulitan Belajar Siswa Kelas VII 2 SMP Negeri 2 Bantaeng - Kaharuddin Kaharuddin (Jurnal Keguruan dan Ilmu Pendidikan, 2020)
This study aims to determine the improvement of learning achievement for students who have difficulty learning in grade students of SMP Negeri 2 Bantaeng VII.2 academic year 2020/2021. The research was conducted in the second semester of academic year 2020/2021. This research includes guidance and counseling action research (action research). This study was conducted in two cycles. Objects in this study is the difficulty of learning the subjects Physics. Subjects in this study were VII.2 graders who totaled 8 people with learning difficulties. The results obtained from the test results of students' learning. In addition to using the test results to learn, method of collection is done through observation and interviews. In the first cycle, an increase in student achievement but not optimal because the students have not been able to improve the academic achievement that have been determined in accordance KKM school therefore 8 students are given guidance on the second cycle. In the second cycle after re-8 students are given guidance has been able to increase achievement learn seen from the test results of the study 8 students were able to improve performance in accordance with KKM learn that has been determined by the school is 75. Accordingly, application of tutoring services done to improve achievement learning for students who have difficulty learning classes VII.2 SMP2 Bantaeng academic year 2020/2021.